Toward a Revised Understanding of Young Children’s Musical Activities: Reflections from the “Day in the Life” Project - Gillen, Julia; Young, Susan (Current Musicology, 2007)
The tradition of developmental psychology as been of fundamental importance in providing versions of musical childhoods, particularly for the earliest years of childhood. However, in its focus on the individual child and in its search for musical behaviors assumed to be common across all children, developmental psychology has tended to be insufficiently interested in wider cultural processes. At the same time, the disciplines of ethnomusicology, the sociology of music, and popular music and media studies, valuable as they are in describing and theorizing the nature of sociocultural practices in music, have nothing to contribute to our understanding of musical practices in young children’s lives. We suggest, then, that the integration of interdisciplinary accounts of young children’s musical experiences is essential if we are to acquire fuller understandings of their musicality, the diversity o their musical practices, and how they develop musically within heterogeneous contexts.